EEG‐neurofeedback and executive function enhancement in healthy adults: A systematic review - Viviani, Giada; Vallesi, Antonino (Psychophysiology, 2021)
Electroencephalographic (EEG)‐neurofeedback training (NFT) is a promising technique that supports individuals in learning to modulate their brain activity to obtain cognitive and behavioral improvements. EEG‐NFT is gaining increasing attention for its potential “peak performance” applications on healthy individuals. However, evidence for clear cognitive performance enhancements with healthy adults is still lacking. In particular, whether EEG‐NFT represents an effective technique for enhancing healthy adults' executive functions is still controversial. Therefore, the main objective of this systematic review is to assess whether the existing EEG‐NFT studies targeting executive functions have provided reliable evidence for NFT effectiveness. To this end, we conducted a qualitative analysis of the literature since the limited number of retrieved studies did not allow us meta‐analytical comparisons. Moreover, a second aim was to identify optimal frequencies as NFT targets for specifically improving executive functions. Overall, our systematic review provides promising evidence for NFT effectiveness in boosting healthy adults' executive functions. However, more rigorous NFT studies are required in order to overcome the methodological weaknesses that we encountered in our qualitative analysis. Neurofeedback is a noninvasive training tool for self‐regulating oscillatory brain activity. Its beneficial effects on cognition are still debated. This systematic review evaluates available evidence on the ability of neurofeedback to boost high‐level cognitive functions. Although some protocols seem to work better than others, more rigorous research is needed.